Spreading Consensus: Correcting Misperceptions about the Views of the Medical Community Has Lasting Impacts on Covid-19 Vaccine Take-up - Vojtech Bartos; Michal Bauer; Jana Cahliková; Julie Chytilová (Center for Economic Studies and ifo Institute (CESifo), 2022)
Identifying sources of vaccine hesitancy is one of the central challenges in fighting the Covid- 19 pandemic. In this study, we focus on the role of public misperceptions of doctors' views. Motivated by widespread concern that media reports create uncertainty in how people perceive expert opinions, even when broad consensus exists, we elicited trust in Covid-19 vaccines held by 9,650 doctors in the Czech Republic. We found evidence of a strong consensus: 90% of doctors trust the vaccines. Next, we conducted a nationally representative survey (N=2,101), and document systemic misperceptions of doctors' views: more than 90% of respondents underestimate doctors' trust; the most common belief is that only 50% of doctors trust the vaccines. Finally, we integrate randomized provision of information about the true views held by doctors into a longitudinal data collection, and regularly measure its impacts on vaccine take-up during a nine-month period when the vaccines were gradually rolled out. We find that the treatment recalibrates beliefs and leads to a lasting and stable increase in vaccine demand: individuals who receive the information are 4 percentage points more likely to be vaccinated nine months after the intervention. This paper illuminates how the engagement of professional medical associations, with their unparalleled capacity to elicit individual views of doctors on a large scale, can help to create a cheap, scalable intervention that corrects misperceptions and has lasting impacts on behavior.
Keywords: C93; D83; I12; 330; Covid-19 vaccine; beliefs; misperceptions; expert consensus; information